2020
DOI: 10.1093/rpd/ncaa057
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Collimation Significantly Improves Lumbar Spine Radiography

Abstract: Purpose To determine the influence of optimal collimation during lumbar spine radiography on radiation dose and image quality. Material and methods 110 lumbar spine patients were split into two groups—the first imaged with standard collimation and the second with optimal collimation. Body mass index, image field size, exposure conditions and dose area product were measured. Effective and absorbed organ doses were calculated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Therefore, the image quality benefits of collimation may be more obvious with smaller regions of interest, for example, the canine shoulder or elbow, where larger differences between optimal and extended collimation are possible. It is well-accepted that collimation size can influence image quality as described and demonstrated by Karami et al ( 20 ) and Pazanin et al ( 21 ) who concluded that optimization of collimation resulted in a reduction of the primary collimation field of 40% and in improved image quality, with a significant difference of 24% in 55 patients.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the image quality benefits of collimation may be more obvious with smaller regions of interest, for example, the canine shoulder or elbow, where larger differences between optimal and extended collimation are possible. It is well-accepted that collimation size can influence image quality as described and demonstrated by Karami et al ( 20 ) and Pazanin et al ( 21 ) who concluded that optimization of collimation resulted in a reduction of the primary collimation field of 40% and in improved image quality, with a significant difference of 24% in 55 patients.…”
Section: Discussionmentioning
confidence: 94%
“…In this study and for all radiographic examinations included, the actual field size was not retrievable owing to the unavailability of the field collimation details in the DICOM header of each image and the possible improper electronic collimation, which may have hidden the actual field dimension of the irradiated body part [24]. Possible systematic patient overexposure due to poor collimation practices may have been concealed with the use of the electronically collimated radiograph for diagnosis [24,[27][28][29][30]. However, it cannot be determined whether the marked increase in the DAP values observed in lateral thoracic spine and lumbar spine examinations is attributable to high dose value or a large field size or both, as field size information is unavailable.…”
Section: Discussionmentioning
confidence: 95%
“…Papers describing optimisation techniques in lumbar spine radiography have been studied in several countries around the world. Those countries are Finland (16), Australia (17,34,39,41), Ireland (18,19,21,22,25), China (20), Sweden (24,26,33), Kuwait (23), United Kingdom (27,30,36), Slovenia (28,35,37), Iran (29,32), Israel (31), Croatia (38) and Malta (40).…”
Section: Results Analysismentioning
confidence: 99%
“…The research methodology was experimental in almost all studies, except for three studies (16,32,39) in which the research methodology was a retrospective study of lumbar spine images. In most cases, the research was performed on an anthropomorphic phantom (17,20,34,41,(22)(23)(24)(25)(29)(30)(31)33), in a few studies the research was performed on patients only (27,(36)(37)(38), and some of them performed a combined study fi rst on a phantom and then on patients (18,19,21,26,28,35,40). The sample size of the examined patient studies varied from study to study.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation